Applications of computational fluid dynamics in abdominal aortic aneurysms - Sun, Zhonghua (Nova Science Publishers, Inc., 2013)
Abdominal aortic aneurysm is a common vascular disease that affects elderly population. Currently, open surgery still remains as the gold standard technique for treatment of abdominal aortic aneurysm. However, endovascular aneurysm repair, as a less invasive technique, has become widely used in many clinical centres and its effectiveness has been confirmed by many studies when compared to open surgery. Computed tomography (CT) angiography has been regarded as the preferred imaging modality for both pre-operative planning and post-procedure follow-up. However, CT is limited to the visualization of anatomical details, thus it fails to provide information about the hemodynamic effects caused by the implanted endovascular stent grafts. Computational fluid dynamics (CFD) is increasingly used to study the fluid phenomena inside the human vascular system. Applications of CFD in the abdominal aortic aneurysm include assisting in developing better stent graft design; lowering the chances of procedure-related complications such as renal dysfunction or stent graft migration, and providing a good understanding of the fluid-stent graft interaction based on aortic models. This book chapter provides an overview of the abdominal aortic aneurysm and treatment options, with a focus on the endovascular stent graft repair, and the applications of CFD in the abdominal aortic aneurysm pre- and post-stent graft repair.